The Influence of Instagram Celebrity Endorsement on Purchase Intention of Erigo Products - Ferdyan Ilhaam Saputro; Budi Astuti (Cita konsultindo, 2024)
One of the marketing strategies related to social media is the celebrity endorsement strategy. However, there is one aspect that needs to be considered for a business when implementing a marketing strategy in the form of celebrity endorsement, namely the celebrity aspect. This study aims to analyze and examine the influence of celebrity aspects including trustworthiness, product match-up, and attractiveness in triggering purchase intentions with consumer perceptions as a mediator. This study uses a quantitative approach method by distributing questionnaires to 165 respondents of Instagram social media users who know the Erigo fashion brand and know Angga Yunanda as a celebrity endorser. The results of data collection were statistically analyzed using PLS-SEM with SmartPLS software. The results prove that celebrity aspects including trustworthiness, product match-up, and attractiveness have a positive and significant influence on consumer perceptions through Instagram celebrity endorsements. In addition, consumer perception can act as a mediator in the relationship between product match-up and consumer purchase intention. This study also reveals that consumer perceptions can have a positive and significant effect on purchase intentions